2023
DOI: 10.12911/22998993/163308
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Contamination of Local and Imported Rice in Semarang, Central Java, Indonesia

Abstract: This study defined the heavy metal concentration in rice, a commonly consumed staple food in Indonesia that is domestically produced and also imported from other countries due to its high demand. A total of six rice samples, comprising of four domestic and two foreign were randomly taken from Semarang stores and analyzed using the Atomic Absorbance Spectrometer (AAS). The laboratory results revealed that three varieties of rice, two from Indonesia (MW and PW; 0.561 and 0.456 mg/kg, each), and one from the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The variation observed can be attributed to the nature of the soil condition that affects plant absorption. The mean Cr content in all the samples, however, was below standard limits according to WHO/FAO, which has a permissible limit value of 1.3 mg/kg for Cr in food (Al-Khatib et al, 2022), and the foreign and local rice reported in Indonesia (Wahyuningsih et al, 2023). The mean Mn concentration in samples obtained in this study was below standard limits according to the WHO/FAO standard permissible limits, which have a value of 500 mg/kg for Mn in food (Al-Khatib et al, 2022).…”
Section: Resultsmentioning
confidence: 86%
“…The variation observed can be attributed to the nature of the soil condition that affects plant absorption. The mean Cr content in all the samples, however, was below standard limits according to WHO/FAO, which has a permissible limit value of 1.3 mg/kg for Cr in food (Al-Khatib et al, 2022), and the foreign and local rice reported in Indonesia (Wahyuningsih et al, 2023). The mean Mn concentration in samples obtained in this study was below standard limits according to the WHO/FAO standard permissible limits, which have a value of 500 mg/kg for Mn in food (Al-Khatib et al, 2022).…”
Section: Resultsmentioning
confidence: 86%